2017
DOI: 10.1186/s40360-017-0139-4
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanism of cardol, isolated from Trigona incisa stingless bee propolis, induced apoptosis in the SW620 human colorectal cancer cell line

Abstract: BackgroundCardol is a major bioactive constituent in the Trigona incisa propolis from Indonesia, with a strong in vitro antiproliferative activity against the SW620 colorectal adenocarcinoma cell line (IC50 of 4.51 ± 0.76 μg/mL). Cardol induced G0/G1 cell cycle arrest and apoptotic cell death. The present study was designed to reveal the mechanism of cardol’s antiproliferative effect and induction of apoptosis.MethodsChanges in cell morphology were observed by light microscopy. To determine whether the mitocho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 29 publications
0
23
0
1
Order By: Relevance
“…The cytoprotective effect of cardol triene was also reported in normal human lung fibroblast cell line, GM07492A, with the 192.6 ± 6.0 µM 34 . Cardol monoene, however, was reported with a cytotoxicity against the SW620 (CC 50 of 14.18 ± 0.76 µM), KATO-III (CC 50 of 19.06 ± 0.39 µM), HepG2 (CC 50 of 2.23 ± 0.22 µM), Chago I (CC 50 of 2.55 ± 0.18 µM) and BT474 (CC 50 of 13.46 ± 0.14 µM) cell lines 16 , 18 , 35 . Also, the saturated anacardic acid was cytotoxic against K562 and AGS cell lines with the CC 50 s of 25.4 µM and 41.6 µM, respectively 36 .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The cytoprotective effect of cardol triene was also reported in normal human lung fibroblast cell line, GM07492A, with the 192.6 ± 6.0 µM 34 . Cardol monoene, however, was reported with a cytotoxicity against the SW620 (CC 50 of 14.18 ± 0.76 µM), KATO-III (CC 50 of 19.06 ± 0.39 µM), HepG2 (CC 50 of 2.23 ± 0.22 µM), Chago I (CC 50 of 2.55 ± 0.18 µM) and BT474 (CC 50 of 13.46 ± 0.14 µM) cell lines 16 , 18 , 35 . Also, the saturated anacardic acid was cytotoxic against K562 and AGS cell lines with the CC 50 s of 25.4 µM and 41.6 µM, respectively 36 .…”
Section: Discussionmentioning
confidence: 94%
“…Phenolic lipids are amphiphilic molecules containing phenolic rings and long aliphatic chains. Recently, accumulated evidences suggested that phenolic lipids showed a broad spectrum antimicrobials 15 , and anti-cancer 16 activities by disturbing the phospholipid membrane 17 and inducing apoptosis 16 , 18 . One of the major sources of phenolic lipids was cashew nut shell liquid (CNSL) existing as mixture of anacardic acid, cardanol, and cardol head groups and saturated (C15:0), monoene (C15:1), diene (C15:2), and triene (C15:3) tails.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, SBP has potent in-vitro anticancer activity, shown by the induction of apoptosis, and cell cycle arrest in these cell lines [ 102 ]. Kustiawan et al also found that cardol isolated from SBP has been used to treat human colorectal adenocarcinoma cell lines, induced changes in cell morphology, increased the expression of apoptotic proteins (caspase-3 and caspase-9) and also cleavage of pro-caspase-3, pro-caspase-9 and poly (ADP-ribose) polymerase (PARP) [ 92 ]. Therefore, cardol isolated from SBP can induce cancer-induced cell death and could be a potential candidate for developing as an additional cancer therapy.…”
Section: Stingless Bee Propolis (Sbp)mentioning
confidence: 99%
“…The mitochondrial membrane potential in the NRVMs was quantified using the ratiometric fluorescent indicator JC-10 [32,33]. This indicator emits green or red fluorescence when excited with 488 nm light.…”
Section: Altered Mitochondrial Metabolism In Hu-treated Nrvmsmentioning
confidence: 99%